EFEKTIVITAS KOMBINASI HYNOSIS LIMA JARI DAN NADHI SODANA DALAM MENURUNKAN NYERI DISMENOREA REMAJA DI DESA MEKARBUWANA - Karuniadi, I Gusti Agung Manik; Widiastini, Luh Putu; Surya Darma, I Gusti Gede Mayun (Poltekkes Kemenkes Jakarta III, 2025)
Dysmenorrhea is the most prevalent complaint among women during menstruation, and it might diminish productivity. Therapies to alleviate dysmenorrhea encompass breathing relaxation, yoga, aromatherapy, warm compresses, hypnosis, and acupressure. Hypnosis is a technique for engaging with an individual's subconscious mind during a state of relaxation. Hypnosis can stimulate the secretion of endorphin chemicals in the body. Nadhi Sodhana is a nasal breathing technique that enhances overall bodily strength, optimizes the respiratory system, eliminates toxins, facilitates oxygenation, and efficiently expels carbon dioxide. The purpose of this research is to determine the effectiveness of the combination of Five Finger Hypnosis and Nadhi Sodana in reducing the pain of adolescent dysmenorrhea in Mekarbuwana Village. This research used a pre-experimental research design, a one-group pretest-posttest design involving 40 teenage girls who experienced dysmenorrhea in Mekarbuwana Village with a purposive sampling technique with inclusion and exclusion criteria. The research results revealed that 77.5% of the participants experienced moderate pain before receiving the intervention (mean: 4.725). Following the intervention, 66.5% reported experiencing mild pain (mean: 1.375). The bivariate test using Wilcoxon shows that the p-value is 0.000. There is a significant difference in dysmenorrhea pain in adolescents in Mekarbuwana village before and after being given a combination of five-finger hypnosis and Nadhi Sodana. The combination of five-finger hypnosis with Nadhi Sodhana can reduce dysmenorrhea pain in adolescents. This research is expected to serve as a reference for a simple method that adolescents can perform independently to reduce dysmenorrhea using five-finger hypnosis and Nadhi Sodhana.